BIOMASS CONVERSION AND ITS APPLICATIONS - Chinnappan Baskar; Shikha Baskar; Amutha Chinnappan (Pattimura Proceeding, 2017)
High worldwide demand for energy, souring prices of petroleum, and concern over global climate change has led to resurgence in the development of alternative energy that can displace fossil transportation fuel. Biomass is one of the important renewable sources for securing future energy supply, production of fine chemicals and high value biodegradable polymers, and sustainable development. Recently, efforts have been devoted to the conversion of lignocellulosic materials into fine chemicals, biopolymers, and biofuels. Attempts to transfer biomass to produce industrially useful polymers and fine-chemicals by traditional biotechnological approaches have obtained only very limited success. An effective biomass conversion requires the interdisciplinary research field which is a unique combination of biotechnology, chemistry, materials science and engineering, and may ultimately lead to cheap and effective processes for conversion of biomass into useful products such as fine chemicals, biopolymers, and biofuels.